Effect Of Skirt to Circular Footing on Clay Subjected on Vertical Loading - Kusumaningtyas, Nella, Ir. Renaningsih, MT, Anto Budi Listyawan, S.T, M.Sc (2016)
Foundation is an important part in building structure. Designing the foundation has to consider the bearing capacity and the settlement. It is necessary to improve and to investigate either on the soil or on the foundation. This research performed to study the effect of skirt on circular footing to reduce the settlement on clay as the alternative solution. There were nine variation experiment laboratory of the circular footing made of steel diameter 75 mm, 100 mm and 150 mm with length of skirt 100 mm and 150 mm on clay by keeping the similar water content and compaction method. The results show that the skirt is effectively to reduce the foundation settlement on clay which is observed on similar load 1 kN. The observations on L/D ratio on similar diameter also show that the higher L/D ratio the smaller settlement. It is also the observations on settlement 3 mm with similar diameter show that the longer skirt the higher load which arrested by the footing. Keywords: foundation, circular footing, clay, settlement, skirt.